Tax Regulations On Cryptocurrency Transactions In Indonesia - Galant, Narwastu Vivaldi; Himawan, Michelle Zefanya; Fitiriyanti, Putri Ayu Delia; Mahadianto, Moh Yudi (Al-Makki Publisher, 2024)
This study explores the evolving landscape of cryptocurrency taxation in Indonesia, focusing on regulatory developments and challenges. Tracing the trajectory from the introduction of Bitcoin in 2009 to the establishment of a formal crypto exchange in 2023, this research emphasizes the government's commitment to regulate and facilitate crypto asset trading. Despite this progress, challenges such as regulatory uncertainties, security concerns, necessitating a profound understanding of cryptocurrency dynamics to navigate the global financial landscape. This research focuses on exploring Indonesia's regulatory response, particularly in taxation, employing a qualitative descriptive methodology that integrates primary data from legal frameworks and secondary data through literature reviews, document analyses, and interviews with cryptocurrency traders and tax officials. This study contributes not only to academic discourse but also provides insights for fostering the growth of the cryptocurrency ecosystem while managing potential tax-related risks.